Correlation Between Candida Albicans Colonization Growth And The Addition Of 5%, 10% And 40% Dextrose Level On Saboraud Dextrose Agar - Tamara, Abelia; Anggowarsito, Jose L.; Waworuntu, Gladdy L. (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction : Candida albicans is normal flora that can be found on skin, oral mucosa and digestive tract. This organism are commensal or non pathogenic, but when there is other predisposition factor, this commensal tendency may become pathogenic to the human body. In Diabetes Mellitus patients with high blood sugar level can affect Candida Albicans infection events. Aim: The purpose of this research is to prove whether there is a correlation between Candida Albicans colonization growth and the addition of 5%, 10% and 40% Dextrose level on Saboraud Dextrose Agar (SDA). Method: This research is a true experimental research with post test only group design observed in 11 days. Samples are from 15 strains of Candida Albicans cultured in Saboraud Dextrose Agar without the addition of Dextrose, with the addition of Dextrose 5%, 10% and 40% in eleven days and the development were noted. The growth of Candida albicans is observed from the diameter growth. Result: in the culture of Candida albicans in 11 days. Data analysis using Kruskal Wallis with data signification (α = 0,05) obtained P 0,000 (P